Profil Kompetensi Guru Sekolah Menengah Kejuruan Teknik Otomotif di Kabupaten Sleman - Lilik Chaerul Yuswono; Martubi Martubi; Sukaswanto Sukaswanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of the study were (1) to determine specific teachers’ pedagogical competencies for practices learning; (2) to assess the teachers’ professional competencies (3) to assess the teachers’ commitment; and (4) to analyse the relationship between the commitment and the pedagogical and professional competencies of Light Vehicle Engineering teachers at SMK in Sleman regency. The data was obtained using questionnaires and observation sheets. The data was analysed using descriptive statistics in precentages with qualitative descriptive explanation. The results of this study show: (1) The mean scores of pedagogical competencies for the preparation and the learning process were 83.58 and 80 respectively (2) The mean score of professional competencies was 2.459, while the scores higher and lower than the mean score were 75% and 25% respectively (3) the mean score of teachers’s commitment was 79.1 while the scores higher and lower than the mean score were 58% and 42% respectively (4) The relationship between the teachers’ commitment with the ability to organise lesson plans, the learning process and the professional competencies were 33.3%, 16.7%, and 41.2% respectively.